Editorial: A South-South exchange begins to re-frame historic dialectical exclusions into situated heritage discourses of reflexive re-imagining - Rosa Guadalupe Mendoza-Zuany; Soul Shava (Environmental Association of Southern Africa, 2019)
The environments in which indigenous communities live have been sustained through complex interactions over centuries. Since the advent of colonial modernity, however, these interactions have experienced change and risk. In education for sustainability, these indigenous environments can be read as changing social-ecological landscapes which both sustain diverse livelihood practices and exhibit the escalating challenges of late modernity. This Special Issue of the Southern African Journal of Environmental Education (SAJEE) focuses on the intergenerational knowledge and livelihood practices of indigenous communities who - often marginalised and facing ever-narrowing prospects of future sustainability - are confronted with an education system that is a relic of colonial modernity and devoid of any social-ecological heritage to which they can relate. Environmental educators and researchers are therefore asking questions concerning colonial modernity in current educational practices, such as: - What can be done to address the predominantly reified and disembedded curricula offered in school and post-school contexts today? - What is the value of bringing local, indigenous and intergenerational heritage and knowledge practices into the curriculum? - How can this inclusion be done in pluralistic and intercultural ways? It is precisely these themes and topics that are addressed in this Special Issue's research, viewpoint and think-piece papers. Many of the contributions have emerged from an international collaboration around Education for Sustainable Development (ESD) through the ESD Expert.Net programme.